AXL inhibitors selected by molecular docking: Option for reducing SARS-CoV-2 entry into cells - Galindo-Hernández Octavio; Vique-Sánchez José Luis (Acta Pharmaceutica)
The COVID-19 pandemic is ongoing and the benefit from vaccines is still insufficient since COVID-19 continues to be dia g-nosed in vaccinated individuals. It is, therefore, necessary to propose specific pharmacological treatments against COVID-19. A new therapeutic target on the human cellular membrane is AXL (anexelekto), proposed as an independent pathway by which interaction with the S protein of SARS-CoV-2 allows the virus to enter the cell, without the participation of ACE2. AXL serves as another gate through which SARS-CoV-2 can enter cells. Therefore, any stage of COVID-19 could be ameliorated by hindering the interaction between AXL and SARS-CoV-2. This study proposes ten compounds (1–10), selected by mole-cu lar docking and using a library of nearly 500,000 compounds, to develop a new drug that will decrease the interaction of AXL with the S protein of SARS-CoV-2. These compounds have a specific potential site of interaction with AXL, between Glu59, His61, Glu70 and Ser74 amino acids. This site is necessary for the interaction of AXL with the S protein. With this, we propose to develop a new adjuvant treatment against COVID-19.